Study of Defective Few-Layer Graphene Intercalated with Lithium - Ilyin, A.M.; Kudryashov, V.V.; Guseinov, N.R.; Toganbayeva, L.K. (Recent Contributions to Physics, 2016)
This paper presents results of computer modeling and quantum mechanical calculations of nanoscaled few-layer graphene (FLG) cells, containing lithium. The results obtained show the essential improvement of physical properties and mechanical dimension stability, in particular, the stiffness of these nanostructures by so called bridge-like defects. It can be supposed, that preliminary radiation modification of FLG nano-cells with formation of such structural defects might become a key technology by production Li-based energy sources and electrical batteries.